2012
DOI: 10.1074/jbc.m112.351395
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 11 Differentially Couples to Histone Acetyltransferase and Histone Methyltransferase Chromatin Remodeling Pathways to Transcriptionally Regulate Dopamine D2 Receptor in Neuronal Cells

Abstract: Background: Chromatin-mediated events utilized by Krüppel-Like factors in neurons remain undefined.Results: Krüppel-Like factor 11 couples to antagonistic chromatin pathways (p300 versus heterochromatin protein 1) to regulate the dopamine D2 receptor gene.Conclusion: This is the first description of mechanisms underlying Krüppel-like factor-mediated functions in neurons.Significance: This knowledge expands our understanding of chromatin-mediated mechanisms that influence homeostasis in highly specialized cells. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 40 publications
(51 reference statements)
1
42
0
Order By: Relevance
“…In support of our findings, p300/CBP has been shown to contribute to the survival, differentiation and neurite growth of a variety of neuronal cell types in the nervous system in vitro and in vivo (Chatterjee et al 2013;Chen et al 2010;Cong et al 2005;Culmsee et al 2003;Gaub et al 2011;Gaub et al 2010;Koyano-Nakagawa et al 1999;Lee et al 2009;Morikawa et al 2005;Rouaux et al 2003;Seo et al 2012;Sun et al 2001;Tsui et al 2014;Wang et al 2010;Wong et al 2005). In terms of the development of midbrain DA neurons, which progressively degenerate in PD, there is evidence to suggest that p300/CBP contributes to the acquisition of a DA phenotype in differentiating neurons (Seo et al 2012).…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of supporting
confidence: 84%
See 1 more Smart Citation
“…In support of our findings, p300/CBP has been shown to contribute to the survival, differentiation and neurite growth of a variety of neuronal cell types in the nervous system in vitro and in vivo (Chatterjee et al 2013;Chen et al 2010;Cong et al 2005;Culmsee et al 2003;Gaub et al 2011;Gaub et al 2010;Koyano-Nakagawa et al 1999;Lee et al 2009;Morikawa et al 2005;Rouaux et al 2003;Seo et al 2012;Sun et al 2001;Tsui et al 2014;Wang et al 2010;Wong et al 2005). In terms of the development of midbrain DA neurons, which progressively degenerate in PD, there is evidence to suggest that p300/CBP contributes to the acquisition of a DA phenotype in differentiating neurons (Seo et al 2012).…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of supporting
confidence: 84%
“…In terms of the development of midbrain DA neurons, which progressively degenerate in PD, there is evidence to suggest that p300/CBP contributes to the acquisition of a DA phenotype in differentiating neurons (Seo et al 2012). …”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 99%
“…We have previously deduced indirectly through the study of KLF10-deficient lymphocytes that KLF10 likely plays a role in the recruitment of PCAF to the core promoter and induction of FOXP3 in adaptive Treg cells (40), yet the direct role for KLF10 to alternatively induce or repress FOXP3 expression through the regulation of acetylation/deacetylation of regional nucleosomes is the novel discovery outlined in this report. Our data would suggest that Sin3 repressor function appears to be dominant over PCAF activation; however, we do not formally exclude the possibility that Sin3 binding normally functions as a rheostat of PCAF-induced activation as has been demonstrated for KLF11 and the recruitment of heterochromatin protein 1 (25,30). In this system, PCAF titration experiments do not affect FOXP3 gene activation (data not shown), and PCAF knockdown does not affect Sin3-mediated repression; thus, we favor the interpretation that Sin3 repressor function is dominant over PCAF activation.…”
Section: Epigenetic Regulation Of Foxp3mentioning
confidence: 62%
“…Since KLF11 has been reported to have both Sin3-HDACdependent and HP1-HMT-dependent repressor functions as well as p300-induced activation properties (Zhang et al 2001;Fernandez-Zapico et al 2009;Lomberk et al 2012;Seo et al 2012), we grouped the KLF11-binding sites into putative KLF11-activated sites (loss of H3K27ac in response to KLF11 knockdown) and putative KLF11-repressed sites (gain of H3K27ac in response to KLF11 knockdown). Our results demonstrate that putative KLF11-activated binding sites are highly enriched in the vicinity of brite-selective genes, in particular putative KLF11-activated brite-selective genes.…”
Section: Discussionmentioning
confidence: 99%
“…KLF11 (also called MODY7) is a well-known regulator of pancreatic b-cell function, and human genetic variants have been associated with dysfunctional b cells and diabetes (Neve et al 2005;Bonnefond et al 2011). In nonadipocyte cell lineages, KLF11 regulates several metabolic gene networks and acts as both an activator and a repressor of transcription (Fernandez-Zapico et al 2009;Seo et al 2012;Lomberk et al 2013). Moreover, it was recently shown that KLF11 can activate UCP1 expression in mouse bone marrow-derived stem cells (Yamamoto et al 2010), suggesting that KLF11 could be a browning factor.…”
Section: Browning Of Human Adipocytes Stimulates a Comprehensive Stabmentioning
confidence: 99%